Genetic evidence of regional circulation of Crimean-Congo hemorrhagic fever virus in ixodid ticks from southern Kazakhstan - Berdikulov, Maxat; Maikhin, Kydyrbay; Karibayev, Talgat; Kalkabayev, Kanat; Kazybay, Botagoz; Nissanova, Raikhan; Makhmutov, Abzal; Rametov, Nurkuisa; Abdikalyk, Abishov; Abdrakhmanov, Sarsenbay; Yang, Dong-Kun; Mussayeva, Gulzhan (Frontiers in Veterinary Science, 2025)
IntroductionArthropod-borne viruses (arboviruses) pose a growing threat to livestock and human health across Central Asia. This study aimed to assess the presence and genetic diversity of arboviral pathogens—Crimean-Congo hemorrhagic fever virus (CCHFV), Bluetongue virus (BTV), Schmallenberg virus (SBV), and lumpy skin disease virus (LSDV)—in ixodid ticks livestock in southern Kazakhstan.MethodsA total of 3,281 adult ticks were collected from three regions (Turkestan, Zhambyl, and Kyzylorda) and identified morphologically. Molecular screening was performed using real-time and nested RT-PCR.ResultsCCHFV RNA was detected exclusively in female ticks from the Turkestan region, with Dermacentor pictus showing the highest infection rate (21.05%), followed by Hyalomma anatolicum, Dermacentor marginatus, and Hyalomma scupense. No viral RNA was detected for BTV, SBV, or LSDV.DiscussionPhylogenetic analysis based on partial S and L segments revealed that the Kazakhstani isolates clustered within Asia-1 and Asia-2 genotypes and shared high sequence identity with regional strains from Uzbekistan, Turkmenistan, and China, supporting transboundary virus circulation. These findings provide additional molecular evidence of localized CCHFV activity in livestock-associated ticks in southern Kazakhstan, expanding current knowledge on the virus’s geographic distribution and genetic diversity.